2007
DOI: 10.1093/humrep/dem145
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of reproductive hormones in adult male twins

Abstract: All measured hormones are highly heritable. A difference in the FSH-inhibin B feedback system between DZ twin males and MZ twin males could not be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…Thus, higher levels of testosterone in males lead to increased reproductive fitness early in life while causing decreased fitness later in life due to a higher risk of prostate cancer (Summers and Crespi 2008). Both testosterone (Kuijper et al 2007;Harris et al 1998) and estrogen (Martini et al 2001) are heritable; thus, there is a need for researches to step in and link heritability of reproductive hormones to that of the longevity. Table 1 presents a list of the above musculoskeletal traits that have been extensively studied by several cohort studies, along with their change with age.…”
Section: Biochemical and Endocrine Serum Markersmentioning
confidence: 99%
“…Thus, higher levels of testosterone in males lead to increased reproductive fitness early in life while causing decreased fitness later in life due to a higher risk of prostate cancer (Summers and Crespi 2008). Both testosterone (Kuijper et al 2007;Harris et al 1998) and estrogen (Martini et al 2001) are heritable; thus, there is a need for researches to step in and link heritability of reproductive hormones to that of the longevity. Table 1 presents a list of the above musculoskeletal traits that have been extensively studied by several cohort studies, along with their change with age.…”
Section: Biochemical and Endocrine Serum Markersmentioning
confidence: 99%
“…For example, testosterone has familial correlations and genetic determinants (8 ), and estrogen also correlates with genetic polymorphisms (7,9,10 ). Results of recent studies in twins showed a high heritability of plasma sex hormone concentrations among adult male twins, with heritability of 57% for testosterone (11,12 ).…”
Section: © 2010 American Association For Clinical Chemistrymentioning
confidence: 99%
“…It is important to note, however, that the level of free testosterone is not determined solely by genes, and that in adult men environmental influences account for roughly 50% of the variance in testosterone level. 35,36 Further examination of this relationship will need to establish candidate genetic and environmental factors that influence testosterone levels in order to determine if they indeed interact with APOE genotype.…”
mentioning
confidence: 99%